2020
DOI: 10.35905/almaarief.v2i2.1685
|View full text |Cite
|
Sign up to set email alerts
|

Eksistensi Permainan Tradisional Selodor Pada Era 4.0 di Kota Mataram

Abstract: Permainan tradisional selodor bertujuan melatih keterampilan, ketangkasan, dan kelincahan dengan memainkan permainan tradisional selodor anak banyak melakukan gerakan-gerakan yang mengecoh lawan guna melewati lintasan dan kembali ke titik awal sebagai tanda kemenangan. Penelitian ini bertujuan untuk mengetahui makna dari permainan tradisional selodor dan bagaimana tingkat eksistensi permainan selodor pada era 4.0 di Kota Mataram. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Traditional games are a typical game activity that grows and develops in an area that is full of values that are taught from generation to generation (Asih & El-Yunusi, 2024;Pratiwi & Heni, 2020). Thus, traditional games have become one of the unique cultural treasures of the Indonesian people (Fitriana et al, 2020). According to Cahyani et al (2023), traditional games found in Indonesia are games that originate from the traditions and culture of each region.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional games are a typical game activity that grows and develops in an area that is full of values that are taught from generation to generation (Asih & El-Yunusi, 2024;Pratiwi & Heni, 2020). Thus, traditional games have become one of the unique cultural treasures of the Indonesian people (Fitriana et al, 2020). According to Cahyani et al (2023), traditional games found in Indonesia are games that originate from the traditions and culture of each region.…”
Section: Introductionmentioning
confidence: 99%